2021
DOI: 10.1111/jace.17945
|View full text |Cite
|
Sign up to set email alerts
|

Broadening emission band of Yb:LuScO3 transparent ceramics for ultrashort pulse laser

Abstract: Sesquioxides were considered as promising gain medium for high power ultrafast laser. Broadening of emission spectrum plays a crucial role in shortening the pulse width of laser. In this paper, the ratio of lutetium oxide and scandium oxide was adjusted to control the emission wavelength and spectral width. Highly sinterable | 6065 WANG et Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The resonator losses in cw MM operation were measured using the method introduced by Caird et al [13], as shown in Fig. 6.…”
Section: Resonator Lossesmentioning
confidence: 99%
“…The resonator losses in cw MM operation were measured using the method introduced by Caird et al [13], as shown in Fig. 6.…”
Section: Resonator Lossesmentioning
confidence: 99%
“…For the cubic-phase mixing of rare-earth sesquioxides, mixing RE 2 O 3 (RE = Lu, Y, Sc) hosts attracts wide research attention because there is no absorption from the visible to infrared wavebands. The Yb:LuScO 3 , Yb:YScO 3 , and Yb:LuYO 3 mixed single crystals show nearly two times of emission bandwidths (22–24.5 nm) in comparison to Yb 3+ -doped RE 2 O 3 (RE = Lu, Y, Sc) and are even broader than that of the ternary mixed Yb:(LuScY) 2 O 3 crystal (18 nm). ,, In addition, the following research studies in Yb 3+ -doped mixed cubic rare-earth sesquioxide transparent ceramics also show the practical spectral broadening effect caused by the disordered local crystal structure. …”
Section: Introductionmentioning
confidence: 99%